1983
DOI: 10.1111/j.1365-2141.1983.tb01989.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular cooperation in endothelial cell thromboplastin synthesis

Abstract: Endothelial cells from human umbilical veins produce a procoagulant identified as thromboplastin (tissue factor, factor III) when stimulated with the phorbol ester 12-0-tetradecanoyl-phorbol-13-acetate (TPA), phytohaemagglutinin (PHA) or endotoxin, Inducible thromboplastin synthesis (i.e. synthesis of the protein component of thromboplastin, apoprotein III) was totally inhibited by cycloheximide and actinomycin D, indicating that de novo protein and RNA syntheses are necessary. Serum enhanced the induced apopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(106 citation statements)
references
References 13 publications
6
99
1
Order By: Relevance
“…In fact, the antifibrinolytic activity of LPS-MNC could be virtually abolished by an anti-TF monoclonal antibody, by an antibody preventing thrombin-mediated TAFI activation, as well as by the direct TAFIa inhibitor, PTCI. Considering that the monocyte is the only blood mononuclear cell capable of producing TF 19,25 and that the lysis time was prolonged also by a monocyte-enriched preparation, it can be safely concluded that the inhibition of fibrinolysis is ascribable to TF-expressing monocytes. These findings, coupled with the observation that soluble TF also prolonged fibrinolysis time and that the conditioned medium of LPS-MNC failed to inhibit fibrinolysis, makes it unlikely that other cell-derived fibrinolysis inhibitors 22 could have contributed appreciably to the prolongation of lysis time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the antifibrinolytic activity of LPS-MNC could be virtually abolished by an anti-TF monoclonal antibody, by an antibody preventing thrombin-mediated TAFI activation, as well as by the direct TAFIa inhibitor, PTCI. Considering that the monocyte is the only blood mononuclear cell capable of producing TF 19,25 and that the lysis time was prolonged also by a monocyte-enriched preparation, it can be safely concluded that the inhibition of fibrinolysis is ascribable to TF-expressing monocytes. These findings, coupled with the observation that soluble TF also prolonged fibrinolysis time and that the conditioned medium of LPS-MNC failed to inhibit fibrinolysis, makes it unlikely that other cell-derived fibrinolysis inhibitors 22 could have contributed appreciably to the prolongation of lysis time.…”
Section: Discussionmentioning
confidence: 99%
“…19,25 In vivo, under a variety of pathophysiological conditions, fibrin formation is induced by TFexpressing monocytes/macrophages adhering to the extracellular matrix. [15][16][17] To see whether adherent activated monocytes influence fibrinolysis we tested monocyte-enriched preparations isolated by adherence to plastic.…”
Section: Inhibition Of Fibrinolysis By Lps-stimulated Adherent Monocytesmentioning
confidence: 99%
“…Endothelial cells inhibit thrombosis by synthesis of prostacyclin (1), plasminogen activator (2), and thrombomodulin (3), and by the presence of antithrombin III cofactor activity (4); they have the potential to support coagulation by generation of tissue factor (5), von Willebrand factor (VWF)' (6), and thromboxane (7). Recently, there has been increased interest in clot-promoting activities of endothelium, and we and other groups reported that Factors IX, IXa, X, and Xa bind to bovine aortic endothelial cells in culture (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Wehave reported previously that the severity of DIC in patients with acute leukemia is correlated to the TF activity of bone marrowcells on admission (9). Lyberg and associates (10) (1 1, 12). In the present study, in order to investigate leukemic cells mainly belonging to the second category, we assessed the response ofleukemic cell TF activity to endotoxin in 43 patients with various types of leukemia, and evaluated the clinical implications with regard to the development of DIC.…”
Section: Introductionmentioning
confidence: 99%